Optical Humidity Sensor Based on Tapered Fiber with Multi-walled Carbon Nanotubes Slurry - Habibah Mohamed; Ninik Irawati; Fauzan Ahmad; Mohd Haniff Ibrahim; Sumiaty Ambran; Mohd Azizi Abdul Rahman; Sulaiman Wadi Harun (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
We demonstrated performance comparison of optical humidity sensor for bare and Multi-walled carbon nanotubes (MWCNTs) slurry coated tapered optical fiber. The starting material for MWCNTs slurry is MWCNTs- acrylonitrile butadiene styrene (ABS) based fused deposition modeling (FDM) 3D printer filament. The ABS was dissolved using acetone to produce MWCNTs-acetone suspension. The MWCNTs-acetone suspension was drop-casted on the tapered fiber to produce MWCNTs slurry by evaporation process at room temperature, which resulted the MWCNTs slurry attach to the tapered fiber. The MWCNTs slurry acts as the cladding for humidity changes measurement. The experimental works showed improvement of sensitivity from 3.811 μW/% of bare tapered fiber to 5.17 μW/% for the coated tapered fiber with MWCNTs slurry when the humidity varied from 45% to 80%.